The Legal Liability of Online Lending Service Providers from the Perspective of Personal Data Protection in Indonesia - Clarrance Mackinnley Filan; Fajar Sugianto (International Journal of Social Service and Research, 2026)
The development of online loan services in the digital economic ecosystem has increased people's access to financing, but has also raised serious problems regarding the protection of personal data in billing practices. This research aims to analyze the juridical qualifications for disseminating debtors' personal data in the online loan collection process and examine the form of legal responsibility of organizers as data controllers. This normative legal research uses a statutory and conceptual approach, analyzing primary and secondary legal materials through systematic and teleological interpretation to assess unlawful data acquisition or disclosure and corporate responsibility attribution. The research results show that the practice of accessing and disseminating personal data to third parties in the billing process has the potential to fulfill the elements of an unlawful act if it is carried out intentionally and causes harm to the data subject, because it is contrary to the principles of legality, purpose limitation and proportionality in data processing. Furthermore, if the action is carried out within the scope of business activities and for the benefit of the corporation, then responsibility can be imposed on the legal entity as the data controller, so that the practice of collecting online loans is not only a contractual issue, but also a violation of privacy rights which demands corporate accountability within the framework of the rule of law.